How do self-direction and values-drive of protean career orientation determine career outcomes? - Marzena Fryczyńska; Agnieszka Pleśniak (Central European Management Journal)
Purpose – The article shows partial proof for the protean paradox existing outside of the Anglo-Saxon part of the world. We pose questions about the impact of each protean career orientation (PCO) dimension on career outcomes, i.e. objective career success (OCS) and subjective career success including career satisfaction (CS) and perceived employability (PE) of studying employees. Design/methodology/approach – We collected data among postgraduate students (N=239) using a paper-and-pencil questionnaire. We estimated the model using structural equation modeling. Findings – The self-direction of PCO improves CS and PE, but only if a person achieves OCS in the organization. We found the same mediation pattern for the values-drive of PCO but in the opposite direction, i.e. greater orientation on personal rather than organizational values – values-drive of PCO was associated with lesser career outcomes. Interestingly, values-drive had a small and direct impact on PE. Originality/value – This study helps us understand how both dimensions of PCO affect career outcomes differently: objective success and subjective factors like CS and PE among employees who are studying.